Reproductive Health and Reproductive Vulnerability - Bojan Žikić (University of Belgrade, 2016)
Reproductive health represents, almost to an equal extent, a socio-cultural and a medical fact. What influences it, both positively and negatively, stems from the ways in which we culturally cognize and act with regard to reproductive behavior. These thoughts and actions are conditioned by a culturally contextualized conceptualization of human physiology which is, in turn, based on the conceptualization of sexuality, and especially, the normativization of gender roles. Therefore, reproductive health is, above all, female health, when viewed as a socio-cultural category, meaning that reproductive vulnerability mostly refers to those factors that negatively influence female reproductive health. These factors are social – they negatively influence reproductive health through the institutional and legally normative aspects, they are economic – they decrease the number of those who, in a certain socio-cultural context, have timely access to quality medical care, and they are cultural – they reinforce modes of thinking and behavior which do not take into consideration the right of every human being to his or her own sexual and reproductive life, but rather insist on conforming individual sexuality and reproductive desires and capacities to the dominant cultural norm.